Evolving Wage Cyclicality in Latin America - Messina, Julian; Gambetti, Luca (World Bank Group, Washington, DC, 2014)
A vector autoregression model with time-varying coefficients is used to examine the evolution of wage cyclicality in four Latin American economies: Brazil, Chile, Colombia and Mexico, during the period 1980-2010. Wages are highly pro-cyclical in all countries up to the mid-1990s except in Chile. Wage cyclicality declines thereafter, especially in Brazil and Colombia. This decline in wage cyclicality is in accordance with declining real-wage flexibility in a low-inflation environment. Controlling for compositional effects caused by changes in labor force participation along the business cycle does not alter these results.